Pidana Mati Perspektif Hukum Islam dan Hukum Nasional - Hakim, Lukman; Hasibuan, Edi Saputra (AL-SULTHANIYAH, 2026)
This study aims to explain the Islamic legal perspective on the implementation of the death penalty in relation to the principles of human rights. The research employs a library-based method with a normative juridical approach and a prescriptive analysis. The focus of the study lies in the concept of al-maṣlaḥah al-mursalah as the foundational principle of Islamic law in determining capital punishment, particularly within the context of qishash. The findings indicate that the death penalty in Islam is not intended as an act of revenge but rather as an instrument for upholding justice and protecting human life in accordance with the maqāṣid al-syarī‘ah, namely the preservation of religion, life, intellect, lineage, and property. Islam also provides space for forgiveness and reconciliation, reflecting a balance between justice and compassion. Thus, the death penalty in Islamic law possesses strong theological and sociological foundations and remains consistent with humanitarian values and the overarching goal of law to promote public welfare.